Whiteness, Man: Whiteness and King of the Hill - Hardy, Maddie (My University, 2018)
I wrote this paper for my Race and Media course, where we were tasked with analyzing the racial imagery in a piece of media of our choosing. Immediately, I knew that I wanted to write about King of the Hill, an underrated show that will always be close to my heart. Drawing on the critical race theory of Michael Brown and Richard Dyer, I argue that King of the Hill subverts hegemonic whiteness by naming the more subversive ways in which whiteness can operate. Whiteness is seen as invisible, as neutral: it has no racial imagery. Dyer argues that this invisibility cements white supremacy by deeming white narratives and experiences to be the universal norm. King of the Hill names this whiteness and creates space for critique. The show uses satire to explore whiteness within blue collar, middle America in a way that doesn’t allow its characters “off the hook” for their racial incompetence. However, unlike Family Guy and other satire peers, King of the Hill does this without relying on overtly racist characters that white audiences can comfortably distance themselves from. The critique of whiteness present in King of the Hill invites white viewers to critically examine their own whiteness and how it functions within society. Just as the show’s characters are not “let off the hook” for their racial incompetence, neither are white viewers. Within the paper, the episodes “Westie Side Story,” “Racist Dawg,” and “Traffic Jam” are analyzed through this critical race theory lens. I had watched King of the Hill as a child, so I really enjoyed revisiting the series from a critical perspective. Reflecting on the show forced me to reflect on my own whiteness and my positionality as a viewer, and I encourage white readers to do the same!
Maddie Hardy’s essay, “Dang Ol’ Whiteness Man: Whiteness and King of the Hill,” opens with a telling quote from the popular Fox television show. As Bobby Hill asks: “Are you sure that white people did all of that stuff? Because I come from white people, and this is the first I’m hearing of it.” Hardy’s essay then takes on the crucial task of interrogating the pernicious notion of racial whiteness as an invisible social norm and accompanying subject position that, as Bobby’s question suggests, couldn’t possibly be involved with the racial problems of the past. What is so interesting and generative about Hardy’s work is that it fleshes out how the subversive, hilarious representational strategies of King of the Hill confronted white viewers in ways that compelled them to rethink their racial identities. Further, though it is clear that Hardy is a fan of the show, the analysis does not shy away from detailed critique, particularly when it comes to portrayals of people of color. The essay nicely assesses moments in which the show reinforces some of the very racial and ethnic stereotypes that it intended to critique. As such, the work deftly accomplished the core objective of my course, COM 301 Race and Ethnicity in Film and Television, that is, for students to identify the roles that popular media play in the production of racial and ethnic ideologies and to weigh the consequences for how we come to understand privilege and power in America.
Keywords: Research -- Periodicals.